Auditory Neural Responses and Communicative Functioning in Children With Microcephaly Related to Congenital Zika Syndrome - Key, Alexandra P.; Powell, Sarah L.; Cavalcante, Juliana; Frizzo, Ana [UNESP]; Mandra, Patricia; Tavares, Adriana; Menezes, Pedro; Hood, Linda J. (Wolters Kluwer, 2024)
Objectives: Children with microcephaly exhibit neurodevelopmental delays and compromised communicative functioning, yielding challenges for clinical assessment and informed intervention. This study characterized auditory neural function and communication abilities in children with microcephaly due to congenital Zika syndrome (CZS). Design: Click-evoked auditory brainstem responses (ABR) at fast and slow stimulation rates and natural speech-evoked cortical auditory evoked potentials (CAEP) were recorded in 25 Brazilian children with microcephaly related to CZS (M age: 5.93 ± 0.62 years) and a comparison group of 25 healthy children (M age: 5.59 ± 0.80 years) matched on age, sex, ethnicity, and socioeconomic status. Communication abilities in daily life were evaluated using caregiver reports on Vineland Adaptive Behavior Scales-3. Results: Caregivers of children with microcephaly reported significantly lower than typical adaptive functioning in the communication and socialization domains. ABR wave I latency did not differ significantly between the groups, suggesting comparable peripheral auditory function. ABR wave V absolute latency and waves I-V interwave latency were significantly shorter in the microcephaly group for both ears and rates. CAEP analyses identified reduced N2 amplitudes in children with microcephaly as well as limited evidence of speech sound differentiation, evidenced mainly by the N2 response latency. Conversely, in the comparison group, speech sound differences were observed for both the P1 and N2 latencies. Exploratory analyses in the microcephaly group indicated that more adaptive communication was associated with greater speech sound differences in the P1 and N2 amplitudes. The trimester of virus exposure did not have an effect on the ABRs or CAEPs. Conclusions: Microcephaly related to CZS is associated with alterations in subcortical and cortical auditory neural function. Reduced ABR latencies differ from previous reports, possibly due to the older age of this cohort and careful assessment of peripheral auditory function. Cortical speech sound detection and differentiation are present but reduced in children with microcephaly. Associations between communication performance in daily life and CAEPs highlight the value of auditory evoked potentials in assessing clinical populations with significant neurodevelopmental disabilities.
Keywords: Auditory brainstem response; Communication; Cortical auditory evoked response; Microcephaly; Prenatal exposure; Zika virus